SIGNIFICANCE OF LEARNING ORGANISATION IN HOSPITALITY AND RETAIL INDUSTRIES – IMPLICATIONS TO HUMAN RESOURCE MANAGEMENT - Ka Shing, LAU (International Journal of Psychosocial Rehabilitation, 2021)
This paper aimed to review previous and recent researches of learning organisation, andorganisational learning in hospitality and retail industries, as well as the implications tohuman resource management, in regard to their roles and strategies to changes, learningenvironment, and organisational competitiveness. Supporting by the present state ofunderstanding on the topic, it tried to demonstrate on a theoretical basis and further studiedin-depth on the research trend of learning organisation related from human resource view.This paper can be a foundation possibly for future development or extension of a newresearch relating to the topic of learning organisation, and further exploration of relevantnew findings. It can potentially contribute to the area of organisational learning with theparticular industries.